INSIGHT ON THE THEROPOD FAUNA FROM THE UBERABA FORMATION (BAURU GROUP), MINAS GERAIS STATE: NEW MEGARAPTORAN SPECIMEN FROM THE LATE CRETACEOUS OF BRAZIL (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2013)
The first bony theropod record from the Campanian Uberaba Formation (Bauru Group) is described. It consists of an isolated caudal centrum (CPPLIP 1324) found in the city of Uberaba, Minas Gerais State, Brazil. The amphicoelous centrum possesses a length to height ratio of 1.74, deep elliptical lateral pneumatic foramen representing 26% of centrum length with three main sub-circular air chambers, andcamellate internal structure.This combination of features is shared with Aerosteon, Megaraptor, and Orkoraptor from the Late Cretaceous of Argentinaand with the Megaraptora indet. fromthe São José do Rio Preto Formation (Bauru Group), São Paulo State,allowing us to refer it to the Megaraptora clade (Tetanurae, Neovenatoridae). As such, the new specimen represents the second megaraptoran from the Late Cretaceous of Brazil and provides new information on tail anatomy on this bizarre group.
Keywords: Uberaba Formation; Megaraptora; Caudal Vertebra; Pneumaticity